Affordable and safe health care for all children: Lessons learned from the use of peg-asparaginase in a developing country - Dhaarani Jayaraman; Ramya Uppuluri; Venkateswaran Vellaichamy Swaminathan; Meena Sivasankaran; Shivani Patel; Revathi Raj (Indian Journal of Medical and Paediatric Oncology)
Peg-asparaginase has widely replaced the use of conventional asparaginase in treatment of children with acute lymphoblastic leukaemia in developed countries. In developing countries like India, with financial constraints being a part of clinical challenge to the treatment of cancers, uniform use of Peg-asparaginase in all children is not practically possible. However, we found by a retrospective analysis of 211 children treated for acute lymphoblastic leukaemia, uniform use of this drug was feasible with indigenous techniques like storing the drug with strict cold chain maintenance and sharing the drug amongst 2 or 3 patients to reduce the burden on each family. We have not found increased rates of infection or any loss of efficacy of the drug due to prolonged storage.